Clima organizacional y su relación con el desempeño laboral de los docentes de la I. E. A. C. “CRISTO REY”, Trujillo - 2018 - Cruzado Loyola, Yharin Milagritos (2019)
ABSTRACT This research work was to establish the relationship between the organizational climate and the work performance of teachers of the Joint Educational Institution "Cristo Rey" La Esperanza - Trujillo, from the teaching perception. For which a population sample of 49 professors of the Joint Educational Institution "Cristo Rey" La Esperanza - Trujillo was selected. Two instruments were used: Valuation scale to measure the level of Organizational Climate that measures the dimensions (interpersonal relationships, teamwork and communication) and the Valuation scale to measure Labor Performance in its dimensions (planning, execution and curricular evaluation). The type of study was descriptive correlational. The Spearman correlation coefficient of 0.851 and a p-value of 0.000 (p <0.05), shows that there is a significant positive relationship between Organizational Climate and Labor Performance in teachers of the Joint Educational Institution "Cristo Rey" La Esperanza - Trujillo.